2022
DOI: 10.3389/feart.2022.843990
|View full text |Cite
|
Sign up to set email alerts
|

Tropical Cyclone Activities Over the Western North Pacific in Summer 2020: Transition From Silence in July to Unusually Active in August

Abstract: In the summer of 2020, tropical cyclone (TC) activities experienced a contrastive transition over the western North Pacific (WNP), from silence in July to unusually active in August. Furthermore, the generation location of TCs was further northwestward in August 2020, resulting in more typhoons landing, and three TCs successively moving northward, which is rare in history. Based on diagnoses with the total genesis potential index (GPI) in July and August 2020, it is suggested that the variation of mid-troposph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…(2022) showed that the MJO had modulated the latitudinal position and intensity of the anomalous anticyclone over the WNP. Particularly in July 2020, the long‐standing MJO in the Indian Ocean favored the WNP anomalous low‐level anticyclone (e.g., Gong et al ., 2022) but this is not the case for June. Wang et al .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…(2022) showed that the MJO had modulated the latitudinal position and intensity of the anomalous anticyclone over the WNP. Particularly in July 2020, the long‐standing MJO in the Indian Ocean favored the WNP anomalous low‐level anticyclone (e.g., Gong et al ., 2022) but this is not the case for June. Wang et al .…”
Section: Resultsmentioning
confidence: 95%
“…Wang et al (2022) showed that the MJO had modulated the latitudinal position and intensity of the anomalous anticyclone over the WNP. Particularly in July 2020, the long-standing MJO in the Indian Ocean favored the WNP anomalous low-level anticyclone (e.g., Gong et al, 2022) but this is not the case for June. Wang et al (2022) noted that the convective episode associated with MJO in July slowly propagated eastward and decayed when encountering the Maritime Continent barrier effect (Zhang & Ling, 2017).…”
Section: Changes In Sst and Low-level Circulationmentioning
confidence: 99%
“…The Western North Pacific (WNP) is the most active ocean basin of tropical cyclone (TC) activity; about one-third of global TCs are generated there (Elsberry 2004;Zhang et al 2016b;Gong et al 2022). The TCs are highly destructive owing to the associated strong wind and heavy rain, and thus often cause huge losses in economic and ecosystem when landing.…”
Section: Introductionmentioning
confidence: 99%